Intracranial Management of Perineural Spread in the Trigeminal Nerve - Redmond, Michael J.; Panizza, Benedict J. (Journal of Neurological Surgery Part B: Skull Base, 2016)
Since the mid-1960s surgeons have attempted to cure intracranial perineural spread (PNS) of cutaneous malignancies. Untreated patients with trigeminal PNS die from brainstem invasion and leptomeningeal disease. It was understood that resection with clear margins was potentially curative, but early surgical attempts were unsuccessful. The prevailing wisdom considered that this surgery failed to improve the results achieved with radiation therapy alone and was associated with high morbidity. However, with improved imaging, surgical equipment, and better understanding of cavernous sinus (CS) anatomy and access, contemporary surgeons can improve outcomes for this disease. The aim of this paper is to describe a technique to access the interdural compartment of the CS and treat PNS of cutaneous squamous cell carcinoma (cSCC) in the intracranial trigeminal nerve and ganglion. It is based on the experience of the Queensland Skull Base Unit, Australia in managing PNS of cutaneous squamous cell carcinoma of the head and neck (cSCCHN).
Keywords: perineural spread; Meckel cave; cavernous sinus; interdural surgery